"How am I doing?" narratives of youth living in congregate care on their social-emotional well-being. (August 2019) - Kelly, Cara; Anthony, Elizabeth K.; Krysik, Judy
Abstract: Youth living in out-of-home placement are presented with a number of challenges to their social-emotional well-being. At minimum, these young people have experienced a disruption to their family and living environment, and in most cases, they have experienced trauma originating from exposure to the abuse and neglect resulting in their out-of-home placement. Despite the complicated emotional consequences of out-of-home placements and the varied experiences that these young people go through, assessment of their social-emotional clinical or behavioral problems deriving from these experiences are rarely self-reported. Thus, an outside perspective limits the ability to understand the social-emotional well-being of these youth and their underlying strengths. This study sought to bridge this gap by investigating how young people themselves define their social-emotional well-being. We identified eight themes through the analysis of 20 individual interviews with youth living in a congregate care placement within the public child welfare system, discussing the implications of the study for practitioners working with these vulnerable young people and critical considerations for the contribution of qualitative methods. Highlights: Qualitative methods enhance our understanding regarding social-emotional well-being among youth residing in out-of-home care Young people residing in congregate care identify their caregivers as important to their social-emotional well-being Youth residing in congregate care struggle with emotional regulation related to the context of their residential settings Despite federal legislation related to normalcy, some youth in congregate care settings perceive implementation as inadequate